2017
DOI: 10.5114/ceji.2017.70975
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution, oxidative stress, and exacerbation of autoimmune diseases

Abstract: A number of epidemiological studies have shown a strong association between exposure to ambient airborne particulate matter (PM 2.5, PM < 1.0) and lung or cardiovascular diseases characterised by high mortality and morbidity. However, much less is known about the role of air pollution in the pathogenesis of autoimmune diseases, which constitutes a significant problem in modern society.This paper summarises the state of current research regarding the influence of PM on the development and/or progression of auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 115 publications
0
55
0
1
Order By: Relevance
“…Increases in the levels of different ROS species may lead to oxidative stress through disruption of the balance between oxidant and antioxidant molecules, leading to tissue damage (to DNA, lipids and proteins [31,32,53](. It has previously been shown that the transcription factor Nrf2 and its related genes are involved in the response to PM exposure [31,32].…”
Section: Early Apoptotic Cells Can Become Late Apoptotic Cells If Thementioning
confidence: 99%
“…Increases in the levels of different ROS species may lead to oxidative stress through disruption of the balance between oxidant and antioxidant molecules, leading to tissue damage (to DNA, lipids and proteins [31,32,53](. It has previously been shown that the transcription factor Nrf2 and its related genes are involved in the response to PM exposure [31,32].…”
Section: Early Apoptotic Cells Can Become Late Apoptotic Cells If Thementioning
confidence: 99%
“…Under inflammatory conditions, production of ROS is tightly correlated to the generation of another group of redox signaling molecules-reactive nitrogen species (RNS) [11]. RNS are derived from nitric oxide (NO), a product of nitric oxide synthase activity.…”
Section: Introductionmentioning
confidence: 99%
“…-особенно если действуют на формирующийся организм с детства, не только способны нарушить развитие легких и дыхательной функции, но и производят системные, в том числе опосредованные через пищу и кишечную микробиоту, эффекты в других органах, вплоть до нарушения психомоторного развития и иммунитета [9,20,28,29,34,36]. Механизмы возможного влияния аэрополлютантов на аутоиммунитет могут быть разными: адъювантоподобное действие, индукция таких модификаций антигенов, к которым не толерантны лимфоциты организма, появление неоантигенов в результате действия активных кислород-и галогенсодержащих радикалов и иных медиаторов воспаления [3,30] и пр. Эффекты при этом могут быть разнонаправленными и нетривиальными: так, недавно в Германии была показана обратная связь между степенью экспозиции озоновому загрязнению и среднесрочной метаболической декомпенсацией СД1, оцененной по количеству гликированного гемоглобина [40].…”
Section: результатыunclassified